A STUDY ON CUSTOMER SATISFACTION TOWARDS ONLINE SHOPPING THROUGH NYKAA IN THOOTHUKUDI (International Journal of Food and Nutritional Sciences, 2022)
Online shopping is a major growth in the field of e-commerce and is certainly the buzz word of shopping across the world. In the present era, all business is managing their business online and initiate necessary steps to sell their products or services online. Online shopping offers a tremendously different shopping experience for people in developing nations like India. Convenience is one of the main reasons for going into online shopping. Large discounts and offers provided by the online sellers also appeal to numerous buyers. This study tries to discover the customer satisfaction towards online shopping through Nykaa in Thoothukudi.